Kebijakan Tax Amnesty dan Program Pengungkapan Sukarela (PPS) serta Implikasinya terhadap Penerimaan Pajak dan Tax Ratio di Indonesia - Yati Mulyati; Diana Sari; Dyah Purnamasari (JURNAL ILMIAH EDUNOMIKA, 2024)
Low tax revenue, the Panama Papers scandal, low taxpayer compliance and taxpayer database collection are the things behind the implementation of the Tax Amnesty program. Indonesia has implemented the tax amnesty program several times, including 1964, 1984, 2016, and 2021. This study aims to determine how the implementation of tax amnesty and the Voluntary Disclosure Program (PPS) and its implications for Indonesia's tax revenue and tax ratio. The research method is carried out with descriptive qualitative. The data used in this research is secondary data in the form of laws, regulations, tax revenue data, and tax ratio. The results illustrate that the tax amnesty program in 1964, 1984 and 2021 was less effective, this is evidenced by the contribution to tax revenue is still minimal. Meanwhile, the tax amnesty program in 2016 had an impact on the increase in tax revenue. The tax ratio is directly proportional to the increase in tax revenue even though the increase does not appear significant.